Sports-related mild traumatic brain injury in female youths. (2nd November 2010) - Keightley, Michelle L; Yule, Ashley; Garland, Kimberley; Reed, Nicholas; McAuliffe, Jim; Garton, Janice; Green, Stephanie; Taha, Tim
Abstract : Sports-related concussion or mild-traumatic brain injury (mTBI) is common in children who participate in organised sports. We describe two case studies involving 14-year-old girls who each sustained a mTBI during ice hockey competition. Neurocognitive functioning post-injury is compared to baseline pre-injury assessment on the same measures. Results from Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT), Conners' Continuous Performance Test II (CPT-II) and the Attention Network Test (ANT) revealed decreased performance in attention, memory functioning and reaction time. Furthermore, some measures had not returned to baseline at midseason testing sessions approximately 30–40 days post-injury. The results are discussed with respect to the difference in recovery profiles and the need for thorough and ongoing evaluation following mTBI in the paediatric population, and for girls in particular.